The empowered manager : positive political skills at work - Block, Peter, (Wiley, 2017)
"Empowerment produces the conditions for high performance. Especially for middle managers and below. Empowered cultures attract and retain talent. They produce high achievement, high accountability and high commitment. The Empowered Manager uncovers a roadmap to creating a more accountable culture in today's fragmented and virtual world. Bestselling author Peter Block is a true visionary: author of the classic Flawless Consulting, his work is about empowerment, stewardship, chosen accountability, and reconciliation of community. In this book, he returns his eye toward management to renew our efforts to create a shift in the traditional hierarchy. Twenty years after the original book, Block talks of why it is so difficult to both open the door to empowerment and more importantly, have people walk through it. It is more important than ever to create a culture in which all members of an organization are treated as entrepreneurs, giving them ownership over their role and responsibilities. This is in the face of the reality that most employees want safety, not the adventure of empowerment. Peter enhances the first edition of the book by acknowledging employees wish for dependency. Their longing for the days when a job carried a promise of a future, and companies cared more about the product and the people, than about the money. This is written primarily for people in the middle. Good managers and employees who care more about doing good work and treating people right, than ambition and making it into the ruling class. The upper middle and below is where there is the greatest need for great management. Which builds on valuing strengths, and allowing talent the space to stretch and achieve. Almost independent of the power points of people at the top. This book shows you how a new approach to management empowers all employees at all levels, and culminates in better business outcomes for the entire organization. Help shape a culture of commitment Develop the political skills to negotiate successfully Take responsibility for your actions Learn to fail up, and face setbacks with courage If you feel controlled by bureaucracy, unrewarded for creativity, and from a distance, powerless to control your own destiny, this book is the breath of fresh air your career has been craving. Timeless tips from a master of business strategy alongside a framework for more effective management makes The Empowered Manager a must-read guide for anyone doing business today"--